Introduction: Enquiries into Contemporary Ritual Landscapes - Pirjo Kristiina Virtanen; Eleonora A. Lundell; Marja-Liisa Honkasalo (Journal of Ethnology and Folkloristics)
‘Landscape’ and ‘ritual’ have been largely discussed in the social and human sciences, although their inter-relatedness has gained li le scholarly a ention. Drawing on earlier studies of ritual and landscape, as well as the authors’ own ethnographic works, ‘ritual landscape’ is suggested here as a useful analytical tool with which to understand how landscapes are produced, and how they, in their turn, produce certain types of being. ‘Ritual landscape’ recognises di erent modalities of agency, power-relation, knowledge, emotion, and movement. The article shows how the subjectivity of other-than-human beings such as ancestors, earth formations, land, animals, plants and, in general, materiality of ritual contexts, shape landscapes. We argue that ways of perceiving landscape includes a number of material and immaterial aspects indicated by ways of moving through landscapes and interacting with di erent human and non-human subjects that come to inhabit the world, creating relations and producing agentive ensembles and complexes.